PENGARUH MODEL PEMBELAJARAN RADEC TERHADAP PEMAHAMAN UNSUR SURAT DAN KEMAMPUAN MENULIS SURAT LAMARAN KERJA SISWA KELAS XII TEKNIK KOMPUTER JARINGAN SMKN 1 BLEGA - Hotijah, Siti; Tobing, Victor Maruli Tua L.; Isman, Soubar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The objectives of this research include: 1) To determine the influence of the Radec learning model on the understanding of letter elements for class 1 Blega, and 3) To determine the effect of the Radec learning model on the understanding of letter elements and the ability to write job application letters for class XII Computer Network Engineering students at SMKN 1 Blega. The approach used in this research uses a quantitative positivism approach. The type of research used in this research is Nonequivalent Control Group Design experimental research. The samples in this research were 22 students in class XII Computer Network Engineering 1 as the control group and 22 students in class XII Computer Network Engineering 2 as the experimental class. In this study, researchers developed two instruments to collect data on understanding letter elements and the ability to write job application letters. Data analysis used independent sample t test and MANOVA analysis techniques. The conclusions of the research results are as follows: 1) There is an influence of the Radec learning model on the understanding of the letter elements of class and 3) There is an influence of the Radec learning model on the understanding of letter elements and the ability to write job application letters for class XII Computer Engineering Network Engineering students at SMKN 1 Blega.